The efficacy of metacognitive and paraphrasing strategy in teaching reading on 11th grade students’ comprehension at SMA Methodist 5 Medan - Barli Tambunan; Anton Purba; Andrew Tobing (Mitra Palupi, 2022)
Background: In search of a solution to the problem that students in Indonesia face in learning English as a foreign language, a strategy called Metacognitive and Paraphrasing strategy is considered to be helpful in helping students develop reading skills. Purpose: This study aims to determine the effect of using the metacognitive and paraphrasing strategy on students’ reading comprehension. Design and methods: This study was conducted by using experimental research. The population of this research was the students of the eleventh grade of SMA Methodist 5 Medan. The sample was 80 students of two classes chosen by using cluster random sampling. They were divided into two groups, 40 students in the experimental group and 40 students in the control group. The experimental group was taught using metacognitive and paraphrasing strategy while the control group was taught using the conventional method. The instrument for collecting data was 20 items of multiple-choice tests. It was given in pre-test and pos-test. After collecting the data, then the researcher analyzed the data by using t-test formula. Results: The finding showed that the t-observe was 4.099 and t-table 1.990 at the level of significance ( α = 0.05 ) and the degree of freedom (df) 78. It means that observe is higher than t-table (4.099 > 1.990). Therefore, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It is proven that there was a significant effect of using metacognitive and paraphrasing strategy on students’ reading comprehension of narrative text.